2017
DOI: 10.2485/jhtb.26.61
|View full text |Cite|
|
Sign up to set email alerts
|

Histological Evaluation of Alveolar Bone Ridge for Dental Implant Placement Using a Nondecalcified Frozen Section Technique

Abstract: Dental implant therapy has been established as an excellent therapeutic method for the recovery of masticatory function. However, no reports to date have undertaken detailed analyses of jaw bone quality using bone biopsy despite the large impact that jaw bone quality at the implant placement sites has on the prognosis of implant therapy. This study histologically examined jaw bone quality at implant placement sites using nondecalcified frozen sections. We also compared bone quality with attenuation (measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Thus, we previously evaluated the osteogenic activity in a study in which a rat calvarial bone defect was covered with the Ti mesh subjected to the MAH treatment, as well as other surface treatments. The results showed that the MAH-treated Ti mesh exhibited the highest bone formation in the bone defect area from an early stage, demonstrating the effectiveness of the MAH treatment on the Ti mesh [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we previously evaluated the osteogenic activity in a study in which a rat calvarial bone defect was covered with the Ti mesh subjected to the MAH treatment, as well as other surface treatments. The results showed that the MAH-treated Ti mesh exhibited the highest bone formation in the bone defect area from an early stage, demonstrating the effectiveness of the MAH treatment on the Ti mesh [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The preparations were digitally photographed with the Nikon photomicrography with a magnification of 509 and assessed manually with the Leica Q-Win Imaging program (McBain Systems, CA, USA). Relative amounts of bone area vs total tissue of the spongious bone were measured as described by Takahashi et al [ 19 ] (% bone area/total tissue (% BA/TA)).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…The idea is to provide spaces using physical means such as barrier membranes that are to be subsequently filled with new bone while preventing other tissues, particularly soft tissues, from inhibiting bone formation. In other words, a space for bone regeneration using membranes with tissue-compatiblity and permeability allows a group of cells derived from surrounding bone tissues to proliferate while preventing competing non-osseous tissues from entering the bone defect site, thereby facilitating generation of new bone tissues [14][15][16] . We guessed that using Ti membrane, which has excellent tissue compatibility, as the membrane could promote bone formation.…”
Section: Results Of Statistical Treatmentmentioning
confidence: 99%